Economic Policy Uncertainty and Monetary Dynamics in Japan: A VAR–EGARCH Analysis - Louis, Gessie (European Scientific Journal, ESJ, 2025)
This paper investigates the impact of economic policy uncertainty (EPU) on money supply, inflation, and financial markets in Japan over the period 2004–2024. Employing a Vector Autoregression (VAR) framework and an Exponential GARCH (EGARCH) model with a student-t distribution, we analyze both the mean and volatility effects of policy uncertainty on key macroeconomic variables. The results show that EPU exerts a considerable influence on monetary dynamics and real economic activity, with persistent feedback effects on industrial production, while its impact on inflation remains modest. Moreover, while volatility modeling reveals no statistically significant direct transmission from EPU to financial market volatility, this finding highlights the conditional, state-dependent, and institution-specific nature of uncertainty propagation in Japan’s financial system. Jointly examining monetary dynamics, real activity, and volatility within a unified time-series framework, this study extends existing literature and provides policy-relevant insights into how central banks can manage uncertainty shocks in a prolonged low-interest-rate environment.